Jatiluhur Reservoir Water Quality Analysis at Various Depths - Eka Wardhani; Zulfah Ananda Sugiarti (Universitas Diponegoro, 2021)
The Jatiluhur Reservoir is an important building in West Java Province whose dams the Citarum River. The location of the Jatiluhur Reservoir, which is the most downstream of the Saguling and Cirata Reservoirs, is where domestic, industrial, and agricultural wastewater pollution is accommodated from water catchment areas so that water quality decreases. This study aims to analyze the water quality in this reservoir at various depths. The study was conducted in September 2020 at 16 sampling points at a depth of 0-8 meters. The water quality parameters analyzed were Temperature, Dissolved Residue (TDS), pH, Dissolved Oxygen (DO), Fluoride (F-), Nitrate (NO3-N), Sulfate (SO42-), BOD5, COD, and Escherichia coli. Based on the study results, it was found that the concentrations of DO, BOD5 and COD at the monitoring location of the Jatiluhur Reservoir did not meet the quality standards. The concentrations of DO, BOD5 and COD respectively 1.00-3.99 mg/L; 3.10-17.00 mg/L; and 28.00-59.00 mg/L. These three parameters contribute to the decline in water quality. The status of water quality using the IP method is categorized as lightly polluted so that it affects the utilization of this reservoir, especially as raw water for drinking water. The highest level of contamination was at the floating net cages sampling location at a depth of 8 m. The decline in water quality in the Jatiluhur Reservoir is caused by organic substances originating from floating net cages waste.